2015
DOI: 10.1080/10256016.2015.997723
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic characterization as a screening tool in authentication of organic produce commercially available in western North America

Abstract: The use of nitrogen stable isotopes to discriminate between conventionally and organically grown crops has been further developed in this study. Soil and irrigation water from different regions, as well as nitrogen fertilizers used, have been examined in detail to determine their effects on nitrogen isotope composition of spinach, lettuce, broccoli and tomatoes. Over 1000 samples of various types of organically and conventionally grown produce of known origin, along with the samples of nitrogen fertilizers use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 33 publications
3
5
0
Order By: Relevance
“…The organic and conventional zucchini samples showed an average δ 15 N value of 5.54 ± 1.10‰ and 2.14 ± 1.64‰, respectively, a higher range of variation being observed for the organically grown vegetables (Table 2). The results from the conventional cultivars were in accordance with those found by previous authors [19,20], who reported respective mean δ 15 N values of 2.32 and 2.40‰, but differed from the values obtained for the organic zucchini samples (above 9‰ in both studies). However, despite the lower differences in the δ 15 N composition between the organic and conventional samples found in our study, we observed statistically significant differences between both cultivars' regimes, although supported by a lower p-value (0.01 > p > 0.05) than those found in the remaining vegetables analysed (p < 0.001).…”
Section: Cucurbitaceaesupporting
confidence: 88%
See 1 more Smart Citation
“…The organic and conventional zucchini samples showed an average δ 15 N value of 5.54 ± 1.10‰ and 2.14 ± 1.64‰, respectively, a higher range of variation being observed for the organically grown vegetables (Table 2). The results from the conventional cultivars were in accordance with those found by previous authors [19,20], who reported respective mean δ 15 N values of 2.32 and 2.40‰, but differed from the values obtained for the organic zucchini samples (above 9‰ in both studies). However, despite the lower differences in the δ 15 N composition between the organic and conventional samples found in our study, we observed statistically significant differences between both cultivars' regimes, although supported by a lower p-value (0.01 > p > 0.05) than those found in the remaining vegetables analysed (p < 0.001).…”
Section: Cucurbitaceaesupporting
confidence: 88%
“…However, the discrimination was less satisfactory for slow-growing vegetables (more than 80 days), hypothesizing that 15 N could be taken by soil microorganisms in situ, reducing the ∆ 15 N between the organic and conventional samples. Another study [20] examined soil, irrigation water, and nitrogen fertilizers used in different conventionally and organically grown crops to determine their effects on the nitrogen stable isotopes of spinach, lettuce, broccoli, and tomatoes. The authors of this study found differences in the δ 15 N of these cultivars according to their organic or conventional management.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, ratios of stable nitrogen isotopes (δ 15 N) in the bulk tissue or in isolated chemical compounds of the foodstuff (e.g. nitrate) have been investigated mainly in fruits and vegetables to detect differences between organic and conventional products . This approach is based on the fact that the nitrogen isotopic composition of synthetic fertilizers, widely used in conventional farming systems, is generally causing lower δ 15 N values compared with animal manures and composts often used in organic systems .…”
Section: Introductionmentioning
confidence: 99%
“…nitrate) have been investigated mainly in fruits and vegetables to detect differences between organic and conventional products. [15,[18][19][20][21][22][23] This approach is based on the fact that the nitrogen isotopic composition of synthetic fertilizers, widely used in conventional farming systems, is generally causing lower δ 15 N values compared with animal manures and composts often used in organic systems. [24] However, different conclusions have been reached in these studies as a consequence of highly different experimental conditions including variation caused by plant species, food products, growth conditions, fertilizer types and application rates and experimental designs.…”
Section: Introductionmentioning
confidence: 99%
“…The lowest δ 15 N value for conventional farming was observed in a batch of tomatoes and was of −2.5‰ [ 15 ] while the highest value, 8.72‰, was observed in peppers [ 19 ] ( Table S1 ). For organic agriculture, the lowest δ 15 N value, 0.3‰, was measured in peas obtained from an organic grocery store [ 20 ] and the highest δ 15 N values, 21.89‰, in lettuce fertilized with bat guano [ 21 ] ( Table S1 ).…”
Section: Resultsmentioning
confidence: 99%